2014
DOI: 10.1071/an14543
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the nitrogen deposition and dietary lysine requirements of Redbro broilers

Abstract: The aim of this study was to determine the coefficients of the Goettingen model for Redbro birds and estimate the digestible lysine requirements. To determine the model parameters, three nitrogen balance trials were performed in Periods I (14–28 days), II (42–56 days) and III (70–84 days), using 42 birds per trial. The birds were individually housed and subjected to six diets with increasing levels of nitrogen, with lysine as the limiting amino acid (deficient by 20% in relation to other amino acids). Dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A validation of the model parameter b as a measure of dietary protein quality, which is independent of the actual level of pro- 2004b, 2004cWecke & Liebert, 2009;Pastor et al, 2013), and it is also can be observed in However, several studies (Daulat et al, 2015;Dorigam et al, 2014;Pastor et al, 2013;Santos et al, 2014;Samadi & Liebert, 2008;Wecke, Pastor, & Liebert, 2016) presented similar characteristics where a decrease in threshold values with increasing age was observed, indicating that the genetic potential is independent of the diet (Samadi & Liebert, 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A validation of the model parameter b as a measure of dietary protein quality, which is independent of the actual level of pro- 2004b, 2004cWecke & Liebert, 2009;Pastor et al, 2013), and it is also can be observed in However, several studies (Daulat et al, 2015;Dorigam et al, 2014;Pastor et al, 2013;Santos et al, 2014;Samadi & Liebert, 2008;Wecke, Pastor, & Liebert, 2016) presented similar characteristics where a decrease in threshold values with increasing age was observed, indicating that the genetic potential is independent of the diet (Samadi & Liebert, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…It is difficult to compare the data with other experiments due to variations in strains, age, feed intake and dietary characteristics. However, several studies (Daulat et al, ; Dorigam et al, ; Pastor et al, ; Santos et al, ; Samadi & Liebert, ; Wecke, Pastor, & Liebert, ) presented similar characteristics where a decrease in threshold values with increasing age was observed, indicating that the genetic potential is independent of the diet (Samadi & Liebert, ).…”
Section: Discussionmentioning
confidence: 93%
“…The values determined to NR max T are difficult to compare with the data of other experiments due to variations in strains, age, feed intake and dietary characteristics. However, several studies with animals in growth (Daulat, et al, ; Dorigam, et al, ; Pastor, et al, ; Samadi & Liebert, ; Santos, et al, ; Wecke et al, ) presented similar characteristics where a decrease of threshold values with increasing age was observed, indicating that animals at maturity tend to have lower values and that the genetic potential is independent of the diet (Samadi & Liebert, ).…”
Section: Discussionmentioning
confidence: 92%
“…However, this is an important parameter used for the modelling procedure of the amino acid requirements (Samadi & Liebert, ). Studies with the Goettingen approach for laying hens are few (Sünder et al, ), but there are already studies with broiler breeder hens (Dorigam et al, ), pullets (Bonato et al, ; Silva et al, ) and broilers in growth phase (Samadi & Liebert, ; Pastor et al, ; Santos et al, ; Daulat, Wecke, Sharifi, & Liebert, , Wecke, Pastor, & Liebert, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation